Soft Power in the Contemporary World: Recommendations to the Small States’ Security - Baniya, Dharma Bahadur (Unity Journal, 2021)
Since the emergence of the New World Order in the international relations, the pursuit of national interests through traditional hard power has come under intense criticism. Employment of military instrument in foreign soil in particular, has been questioned. Examples of Afghanistan, Korean Peninsula, Iraq, and Middle-East demonstrate that hard power approach alone, has been barely successful to handle multi-dimensional security challenges in the contemporary world. Although the hard power remains as important instruments of national power, its employment is becoming less significant due to its legitimacy and effectiveness in the changing global environment. Hence, the concept of soft power has been advanced as an alternative approach because of its potential of securing national interest without using force or coercion. Though the smart power, as an appropriate combination of hard and smart powers, has its implications in the international politics; soft power constitutes a very real power. This article argues on why soft power has been a more relevant instrument for the states being blessed or lacking the military might. Finally, the article presents its analysis with implications and recommends on ways in which small states like Nepal need to resort to soft power to ensure their foreign policy objectives and security in the changing international order.